2022
DOI: 10.1177/09673911221106686
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy-based composites with enhanced thermal properties through collective effect of different particle size fillers

Abstract: Taking advantages of excellent adhesion and insulating properties, polymer-based thermal interface materials have been widely used in electrical and electronic industry. However, applications was limited due to the existence of high interfacial resistance and poor mechanical properties resulted from poor dispersion and weak interfacial adhesion of thermal conductive fillers in the polymer matrix. Herein, different sizes of aluminum oxide microparticle was used as thermal conductive fillers to fabricate a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Previously, it was demonstrated that thermal interface barriers play a major role in setting the performance limits in conventional cooling systems made of aluminum or copper being attached with thermal paste. [11][12][13] The key to dramatically reducing thermal interface barriers is developing new applicable materials which can be printed directly on the substrate.…”
mentioning
confidence: 99%
“…Previously, it was demonstrated that thermal interface barriers play a major role in setting the performance limits in conventional cooling systems made of aluminum or copper being attached with thermal paste. [11][12][13] The key to dramatically reducing thermal interface barriers is developing new applicable materials which can be printed directly on the substrate.…”
mentioning
confidence: 99%